Analisis Framing Berita Pengusiran Mahasiswa Universitas Hasanuddin Yang Mengaku Gender Netral Oleh Media Online Tempo.Co - Syuhada Syuhada; Tessa Shasrini (Lembaga Pengembangan Kinerja Dosen, 2024)
Mass communication, messages are called information or news. In presenting news, every media, especially online media, is required to always present news presentations that are able to attract readers in such a way. Issues in the news are conveyed through various media, one of which is online media. Likewise, Tempo media not only presents literacy media in the form of magazines, but also online media. The development of globalization and information has made it easy for various issues to spread, such as the issue of the existence of various gender terms currently, one of which is gender neutral which has become a news issue and is also an issue taken up by researchers. One of the gender neutral statements occurred in one of the UNHAS students as reported by Tempo.co. This research uses descriptive qualitative research methods. Data collection techniques use observation and documentation. The aim of this research is to analyze the framing in the news about the expulsion of Hasanuddin University students who claim to be gender neutral by the online media Tempo.co using the Pan and Kosicki model based on the classification of four syntactic, script, thematic and rhetorical structures. The results of this research are that if it is concluded from Pan and Kosicki's four structures, there are several points in the news published by Tempo.co, namely first, the pros and cons of gender neutral recognition by a student. Second, the lecturer's attitude violates the code of ethics. Third, Tempo.co's stance is pro gender deviation.